Bisphenol analogues differently affect human islet polypeptide amyloid formation. Issue 9 (18th January 2016) - Huang, Lizi; Liao, Mingyan; Yang, Xin; Gong, Hao; Ma, Liang; Zhao, Yudan; Huang, Kun
Abstract : Bisphenols (BPs) are widely used in the production of plastic material, misfolded human islet amyloid polypeptide (hIAPP) is a causal factor in diabetes. We demonstrated BPs analogues show different effects on hIAPP amyloid formation. Abstract : Bisphenols (BPs) are a group of chemicals with two hydroxyphenyl functionalities. BPs analogues including bisphenol A (BPA), bisphenol B (BPB), bisphenol F (BPF), bisphenol S (BPS), bisphenol AF (BPAF), bisphenol AP (BPAP), tetrabromobisphenol A (TBBPA) and tetrachlorobisphenol A (TCBPA) are widely used in the production of plastic materials. There has been a growing concern worldwide about environmental BPs exposure due to their potential adverse effects on human health. Deposition of β-cell toxic misfolded human islet amyloid polypeptide (hIAPP), a hormone biosynthesized and secreted by the pancreatic β-cells, is a cardinal finding in type 2 diabetes mellitus (T2DM). Epidemiological studies suggest BPA exposure is positively associated with the incidence of T2DM, which may be due to the exacerbated toxic aggregation of hIAPP induced by BPA as we previously reported. Here, we demonstrate that bisphenol analogues showed different effects on hIAPP amyloid formation. Unlike the accelerating effects of BPA, four BPs analogues (BPAF, BPAP, TBBPA and TCBPA) showed inhibitory effects on hIAPP aggregation and decreased the membrane disruption capacity of hIAPP. Our results also explained a possible relationship between the spatial structure and the inhibitory capacities of BPs analogues.